Однойменні Шевченкові вірші «Думи мої, думи мої...»: історія тексту та особливості поетики - Приліпко, І. (Слово і Час, 2022)
У статті висвітлено процес становлення основного тексту віршів Т. Шевченка «Думи мої, думи мої...» 1840-го та 1848-го років написання. Розкрито художні особливості творів, з’ясовано їх ідейно-естетичну суголосність та значення в доробку поета. Простежені зміни на шляху до остаточного тексту обох віршів увиразнюють специфіку творчої лабораторії автора, засвідчують його прагнення вдосконалити граматику і стилістику тексту, виявляють ретельне ставлення поета до форми і змісту своїх творів, до належної їх підготовки до друку. The paper highlights the formation of the main text of T. Shevchenko’s poems “My Thoughts, My Thoughts...” from 1840 and 1848. The research focuses on the literary features of the poems, clarifies the coherence of their ideas and design, emphasizes the significance of these pieces within the poet’s works. Both poems, differing in volume, time, and place of writing, are related not only in title but also in the key motives, images, and their weight in the ideological and aesthetic context of all Shevchenko’s writings. The changes made on the way from the first edition to the main text of the poem from 1840, although insignificant, testify to the author’s desire to improve his text both on the grammatical and semantic levels. The textual history of the poem from 1848 more clearly represents the peculiarities of the creative process, since on the way from the draft autograph to the main text one can trace not cardinal but significant semantic changes that reveal the specifics of the poet’s creative pursuits, his careful treatment for the form and content of the works, and their proper preparation for print. Both poems testify to the invariability of the artist’s ideas and aesthetic guidelines and, at the same time, the creative evolution of his worldview, based on life experience and living conditions. If the importance of the poem from 1840 lies primarily in shaping the author’s literary strategy, as it accumulates key motives and images of Shevchenko’s work, reveals the specifics of the artist’s worldview and creative personality, the poem from 1848 is a result of the experience that made creativity and freedom axiological dominants of the artist’s life.